Reterritorialising paediatric care in general practice clinics through a GP-paediatrician integrated care model - Michael Hodgins; Jenny Sohn; Carmen Crespo-Gonzalez; Tamara Morris; Yvonne Zurynski; Sonia Khano; Lena Sanci; Teng Liaw; Gary Freed; Brendan Goodger; Harriet Hiscock; Raghu Lingam (SSM: Qualitative Research in Health)
Evidence is building exploring the efficacy of general practitioner (GP)-paediatrician integrated care models in improving the quality of paediatric primary care and reducing GP referrals to outpatient clinics and emergency departments. However, contemporary research has not adequately explored the mechanisms of change within these models to best support their sustainability and scalability. Our analysis involved interviews and focus groups with four paediatricians and 82 GPs across 21 general practices that were enrolled in a trial of a GP-paediatrician integrated care model, Strengthening Care for Children (SC4C). Using Deleuze and Guattari's ontological framing of assemblage deterritorialisation and reterritorialisation, we explored how the SC4C model reterritorialised GPs' scope of practice. We framed our reading of GP-paediatrician roles and responsibilities using material forms of content and immaterial forms of expression to identify how the SC4C model disrupted historical relationships and hierarchies between general practice and paediatric domain of practice. Our analysis revealed that the boundaries of GP-led paediatric assemblages of care were often dictated by system constraints within existing GP models, including limited funding and time available for GPs to deliver comprehensive paediatric care.